Beyond Dialogue: Envisioning a Jewishly Enriched Body of Christ. Issue 3 (August 2019) - Shapiro, Faydra
Recently, an intriguing essay appeared in the pages of Pro Ecclesia, a Journal of Catholic and Evangelical Theology, by Thomas Weinandy, entitled "The Jews and the Body of Christ: An Essay in Hope." In his essay, Weinandy notes that "it is impossible to delineate in detail the benefits that would accrue to the Body of Christ through the active presence of the Jewish people simply because the Body of Christ has yet to experience them." This article engages this as an imaginative exercise: What could a robust, Jewishly-infused Christianity actually look like? If there is in fact something Jewish pulsating at the heart of the body of Christ, what would it look like if it were allowed to pump freely, unhindered yet directed, and actually serve to revitalize the body? After all the theologizing, this article asks - and begins to envision a concrete answer to - the question: What is it that Jews, Judaism, the Jewish experience actually have to offer Christianity?